PENGGUNAAN MODEL PEMBELAJARAN TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATERI PERSATUAN DAN KESATUAN BANGSA INDONESIA DI KELAS VB - Unsi, Pitriatul; Muhammad, Marsih; Setyaningrum, Saumi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
The purpose of this study is to describe: 1) Result of learners of the material of the unity of Indonesian before using the make a match type learning model. 2)numbers of steps for the use of the make a match type learning model to improve learning result material of the unity of Indonesian. asil belajar learners material unity and unity of the Indonesian nation after using the make a match type learning model. 4)Whether there is an increase in student learning outcomes material for the unity of Indonesian after using the make a match type learning model in class VB Nuruh Hasanah Islamic Elementary School Sungai Nipah for the 2021/2022 academic year. This research uses quantitative research. Type of classroom action research (PTK). The location ofthe search is Nuruh Hasanah Islamic Elementary School Sungai Nipah. Source of data for class VB learners. Techniques for collecting test data, observation and documentation. Data collection tools for question sheets, observation sheets and digital cameras / cellphones. Data analysis uses mean, percentage and success indicators. The results of this study are: 1) Learning outcomes before using the make a match type learning model to improve learning outcomes of material for the unity of Indonesian in class VB Nuruh Hasanah Islamic Elementary School Sungai Nipahin the 2021/2022 year, namely there are an average of 69.9 and 26% student complate. 2) Steps to use the make a match type learning model to improve learning outcomes of the unity of Indonesiana in class VB Nuruh Hasanah Islamic Elementary School Sungai Nipah for the 2021/2022 academic year in cycle I can be carried out 75%, siklus II is carried out 85% and cycle III is carried out 90% of the stepsh learning carried out. 3) Learning outcomes after using the make a match type learning model to improve learning outcomes of the material for the unity of Indonesian in class VB Nuruh Hasanah Islamic Elementary School Sungai Nipah for the 2021/2022 academic year in cycle I is 46%, siklus II is 53% and siklus III is 88%. 4) There is an increase in learning outcomes after using a make a match type learning model to improve learning outcomes of material for the unity of Indonesian in class VB Nuruh Hasanah Islamic Elementary School Sungai Nipah the 2021/2022 academic year is from cycle I to cycle II has increased by 7%, from cycle II to cycle III experienced an increase of 35% while from cycle I to cycle III experienced an increase of 35% while from cycle I to cycle III experienced an increase of 7%, from cycle II to cycle III experiencedan increase of 35% while from cycle I to cycle III experienced an increase of 35% while from cycle I to cycle III experienced an increase of 35% while from cycle I to cycle III experienced an increase of 35% while from cycle I to cycle III experienced an increase of 35% while from cycle I to cycle III experienced an increase of 35% while from cycle I to cycle III experienced an increase of 7%, from cycle II to cycle III. i an increase of 42%.